A study on the influencing factors of social media in the communication of cultural heritage education : A systematic literature review - Shao, Yubo; Jamal Rizal, Razali; Hasmadi, Hassan; Pan, Bo (Redfame Publishing Inc., 2023)
This study examined the impact of social media on disseminating cultural heritage education. After reviewing two databases, 29 articles met our inclusion criteria. This study found that social media can expand the educational scope of cultural heritage and increase public awareness and interest in cultural heritage tourism sites and museums. However, social media is only a publicity channel. It is necessary to consider five influencing factors in social media: the subject of information distribution, the motivation of distribution, the purpose of distribution, the content of distribution, and the method of distribution, and to analyze the specific practices of social media in disseminating cultural heritage education. Therefore, more research is needed to explore the influence of social media on cultural heritage education dissemination, to explore the educational nature of social media in cultural heritage education communication, and to provide a theoretical basis for social media to promote cultural heritage education dissemination.